(898) Computer and Programming Concepts مفاهيم اجهزة الكمبيوتر ( الحواسب الالكترونية ) والبرمجة - El Gohary,Hassan (INP., 2024)
The study explores the organization of digital computers and introduces the basics of computations using the FORTRAN programming language. It outlines the steps for solving problems using computers, from programming and program testing to production. The study explains the components of FORTRAN programs, including constants, variables, operations, and expressions, as well as mathematical functions. It delves into input/output statements, formatting data, and control instructions like PAUSE, STOP, and END. The use of subscripted variables, the Dimension Statement, loops (DO and Continue), and indexing in input/output lists is also clarified, along with additional input/output instructions. / / تناولت الدراسة تنظيم الحواسيب الرقمية وتقديم الأسس التي تقوم عليها الحسابات باستخدام لغة البرمجة فورتران (FORTRAN). تم استعراض خطوات حل المشكلات باستخدام الحاسوب، بدءًا من البرمجة واختبار البرامج وصولاً إلى الإنتاج. كما تم شرح مكونات برامج فورتران مثل الثوابت والمتغيرات، والعمليات والتعبيرات، والوظائف الرياضية. وتطرقت الدراسة إلى تعليمات الإدخال والإخراج، وبيانات التنسيق، وتعليمات التحكم مثل PAUSE وSTOP وEND. تم توضيح استخدام المتغيرات المؤشرة وبيان الأبعاد (Dimension Statement)، بجانب التعليمات الخاصة بالحلقات (DO وContinue) وطريقة الفهرسة في قوائم الإدخال والإخراج، بالإضافة إلى تعليمات إضافية للإدخال والإخراج